Role of minimum wages in rebalancing the economy. Issue 1 (5th August 2013) - Rani, Uma; Belser, Patrick; Ranjbar, Setareh
Abstract: Minimum wages can be a powerful tool for supporting decent work goals and can be a crucial component to the strengthening of social protection floors and poverty alleviation efforts. This paper argues that effectiveness of minimum wages depends on three aspects: first, on the legal coverage of minimum wage systems; second, the level at which minimum wages are set; and third, the ability to ensure compliance with legal minimum wage provisions, so as to ensure the goal of improving incomes and reducing inequality.